Optimalisasi Peran Pengawasan Otoritas Jasa Keuangan Terhadap Baitul Maal Wa Tamwil Di Yogyakarta - Ani Yunita; Andri Martiana; Riska Wijayanti (Arena Hukum, 2022)
This research aims to determine the problems faced by Financial Services Authority in carrying out the supervisory, and to optimize the role of OJK's supervision in the implementation of BMT operational activities in Yogyakarta. This is empirical normative research. The results show that there are several problems faced by OJK in carrying out its supervisory role, namely inconsistency in legal regulations related to supervision, limited human resources and technology and lack of coordination between BMT supervisory agencies and to optimize the role of OJK's supervision of BMT operational activities in Yogyakarta. First, legal factor, making laws and regulations and their implementing regulations needs to be explained in a detailed manner. Second, DPS needs to be increased further in order to maximize the implementation of the supervisory function. Third, OJK needs to encourage sharia financial service business actors, especially BMTs, to transform LKMS. Fourth, OJK needs support from the culture of the Yogyakarta community who have high Islamic spiritual so it can support the role of OJK supervision and development of BMT in Yogyakarta.